The cost of a combination Anti-Retroviral Therapy (cART) optimization pathway as maintenance therapy in HIV-1 infected patients - Ravasio, Roberto; Rigo, Fabio; Lattuada, Emanuela; Concia, Ercole; Lanzafame, Massimiliano (Farmeconomia. Health Economics and Therapeutic Pathways, 2017)
BACKGROUND: In order to reduce/prevent combination Anti-Retroviral Therapy (cART)-related toxicity, while maintaining its therapeutic effectiveness over time, the optimization of the antiretroviral therapy could be performed. AIM: To estimate the economic impact on the Italian National Health Service (NHS) of a cART optimization pathway as maintenance therapy in HIV-1 infected patients over one-year period. METHODS: Patient data were retrieved from the electronic medical record system in use (year 2015) in a reference HIV Center in Northern Italy. The analysis considered naïve patients and non-naïve patients. To estimate the actual ART expenditure charged to the Center we calculated the cost of cART received during 12 months for each patient. Subsequently, referring to the same patients, a "potential" cART expenditure was estimated. This potential expenditure was estimated taking in consideration the adoption of a specific optimization pathway aimed at maintaining over the time the cART efficacy. Lastly, to assess the sustainability of the optimization pathway, we compared the actual cART expenditure with the potential one. We considered only drug costs (ex-factory prices, included all discounts and VAT) from the perspective of the Italian NHS. RESULTS: In the 2015, the total expenditure for 564 enrolled HIV-1 patients treated with cART was € 4,042,983. The mean treatment cost per patient was € 7,168. If the Center adopted a specific optimization pathway, the total expenditure would be € 3,914,855 (€ -128,128). CONCLUSIONS: From the Italian NHS’s perspective, the adoption of a specific cART optimization pathway represents a cost-saving option as maintenance antiretroviral therapy in HIV-1 infected patients.